KEEFEKTIFAN METODE SILIH TANYA MODEL KOMPETISI BIASA JENIS 1 ANTAR MAHASISWA PADA MATERI RUANG VEKTOR MATAKULIAH ALJABAR LINEAR ELEMENTER SEMESTER V - Dwi Ivayana Sari (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2016)
This study is an experimental study with quantitatively descriptive approach which aims to describe the effectiveness of learning using wondering successive method with regular competition model of type 1 among students on vector space material. The subjects of this study are fifth semester students of mathematical education programe in STKIP PGRI Bangkalan. The Results of study are analyzed descriptively to see the lecturer's ability in managing learning process, student’s activity and the completeness of learning result classical. The results of study show that the used method is effective to implement on vector space material. This conclusion is based on several things, namely (1) the lecturer's ability in managing learning process is effective, student’s activity is effective and the classical completeness of learning result is achieved.